Connecting Chronicles: Material and Social Bonds in the Circulation of the Chronique Abrégée in Fifteenth-Century Paris - Emerson, Catherine (Journal of Historical Network Research, 2023)
In examining the network of owners associated with manuscripts of fifteenth-century French histories and the material connections between the manuscripts themselves, a clear distinction emerges between a group of male historians associated with the French court whose manuscripts were privately owned and other texts subject to public consumption.